Effect Of An Educational Program Using Lift-Movement Theory On Breaststroke Learning Level Of Children Aged (10-12) Years - Saleh Nayef Abdulhaleem (Musamus Journal of Physical Education and Sport (MJPES), 2026)
The current study aimed to investigate effectiveness of an educational program based on lift-action theory in improving breaststroke skill of children aged 10–12 years, based on assumption that gradually reducing motor load in early stages of learning contributes to building more precise and stable motor patterns. The researcher adopted an experimental approach with a single-group pre- and post-test design, given the nature of educational environment at Maarif Academy in Baghdad. The sample consisted of 27 children who had never received formal breaststroke instruction. The program lasted 8 weeks, with 3 sessions per week, each session lasting 60 minutes. It included progressive stages starting with partial motor support and ending with full independent performance. Skill performance was measured using a standardized technical assessment form, in addition to a time test for completing 25m breaststroke. Results showed statistically significant differences at level of α ≤ 0.05 in favor of post-test in skill performance t = 12.84. Completion time t = 9.73 and effect size Cohen’s d were high, indicating a strong impact of the program. Results suggest that applying modern motor learning principles, as described by Schmidt & Lee (2019) and Magill & Anderson (2017), contributes to improving motor learning efficiency in aquatic environments. The study recommends adopting the proposed educational model in children’s swimming programs.